Determination of metals in plant foods produced in the irrigated perimeters Jacarecica I and Macela dam in Sergipe (Research, Society and Development, 2022)
The knowledge about the interactions between plants and heavy metals is very important, not only had the safety of the environment, but also to reduce the risks associated with the introduction of these elements in the food chain. This study determined the concentration of metals in cultivars produced in irrigated areas Jacarecica I and Macela Dam in Itabaiana-SE. The quantification of metals Zn, Cu, Ni, Cr, Pb, Mn, Fe, Na, K, Mg and Ca was made by Atomic Absorption Spectrometry. The results in vegetables were expressed as a function of wet mass. The data set obtained with the mean concentrations in vegetables was subjected to exploratory data techniques, principal component analysis (PCA) and hierarchical cluster analysis (HCA) promoting the separation of vegetables according to their type, showing that there is a predominance in metal concentrations in vegetables of roots.